Variant rs1801157 in the 3'UTR of SDF-1ß does not explain variability of healthy-donor G-CSF responsiveness. - Miriam Schulz; Darja Karpova; Gabriele Spohn; Annette Damert; Erhard Seifried; Vera Binder; Halvard Bönig (PLoS ONE, 2015)
The genetics responsible for the inter-individually variable G-CSF responsiveness remain elusive. A single nucleotide polymorphism (SNP) in the 3'UTR of CXCL12, rs1801157, was implicated in X4-tropic HiV susceptibility and later, in two small studies, in G-CSR responsiveness in patients and donors. The position of the SNP in the 3'UTR together with in-silico predictions suggested differential binding of micro-RNA941 as an underlying mechanism. In a cohort of 515 healthy stem cell donors we attempted to reproduce the correlation of the CXCL12 3'UTR SNP and mobilization responses and tested the role of miR941 in this context. The SNP was distributed with the expected frequency. Mobilization efficiency for CD34+ cells in WT, heterozygous and homozygous SNP individuals was indistinguishable, even after controlling for gender. miR941 expression in non-hematopoietic bone marrow cells was undetectable and miR941 did not interact with the 3' UTR of CXCL12. Proposed effects of the SNP rs1801157 on G-CSF responsiveness cannot be confirmed in a larger cohort.